WHEN INDIVIDUALS HOLD RELIGION AS A COPING TOOL: A QUALITATIVE STUDY OF ACCULTURATION PROCESS IN SYRIAN REFUGEES WITH DISABILITIES - Sağır, Zeynep (My University, 2019)
This study focuses on disabled asylum-seekers, who are often ignored among immigrants butnevertheless encounter many difficulties. The objective of this study is to understand the role ofreligion in their efforts to overcome the difficulties they face. In order to get first-hand and in-depthaccounts, qualitative research methods were used. There were two groups of participants -- sixdisabled Syrians as the test group and six disabled Turks as a control group. Semi-structuredinterviews were conducted. The data were analyzed via NVIVO-11 program.Disabled asylum seekers are at risk in various ways. Importantly, the results show that the religiousaspects of their lives are the most important elements that they attach to life. Religious supporthelps them overcome the hardships they face. There seem to be two reasons for this: First, thereligious support is received at no cost to the individual; second, the religion the disabled Syriansbelieve and practice constitutes the most important point of cultural similarity to the culture ofTurkey.
Keywords: Sosyal Çalışma; Din Bilimi; Kültürel Çalışmalar; Aile Çalışmaları